Factors affecting occupational black carbon exposure in enclosed railway stations. (15th November 2022) - Delgado-Saborit, Juana Maria; Lim, Shanon; Hickman, Alice; Baker, Chris; Barratt, Benjamin; Cai, Xiaoming; Font, Anna; Heal, Mathew R.; Lin, Chun; Thornes, John E.; Woods, Michael; Green, David
Abstract: Many rail services around the world continue to use diesel as the primary fuel source and enclosed railway stations have been identified as a possible hotspot for exposure to harmful diesel exhaust exposures. Little is known about the occupational exposure to air pollution for railway station workers due to their mobility around the station and variations in station design. A detailed understanding of the concentration of black carbon (BC), a diesel exhaust tracer, inside railway stations and the factors driving occupational exposures is required to minimize occupational exposure. Real-time personal exposure to BC was measured during 60 work-shifts encompassing different roles at three large enclosed railway stations of different design in London, Birmingham and Edinburgh (UK). Sampling was conducted by the train station workers over a period of 27 days between January 2017 to October 2018. Worker shift-mean BC exposures ranged 0.6–20.8 μg m −3 but 1-min peak exposures reached 773 μg m −3, with train dispatchers experiencing the highest BC exposures. Station design, job role, and frequency of diesel trains were the main drivers of occupational BC exposure. Elevated exposures for some station workers indicate that mitigation measures to reduce their exposure should be implemented to lower the risk of occupational health impacts. These could include improving ventilation and reducing engine emissions. Graphical abstract: Image 1 Highlights: Station design, job role, diesel train frequency are main drivers of occupational BC exposure. Occupational BC exposures in enclosed train stations is the highest. Dispatchers had the highest work-shift mean exposures. Idling diesel trains contribute to elevated occupational exposures to BC. Elevated exposures for some job roles indicate the need of mitigation measures.